Narrowing Proficiency Gaps in Heterogeneous Secondary EFL Classrooms with Cooperative Learning - Hudriati, Andi; Syamsu, Awaluddin; Selfiyanti, Selfiyanti (ELT Worldwide: Journal of English Language Teaching, 2025)
Heterogeneous proficiency remains a persistent challenge in English as a Foreign Language (EFL) classroom, where students’ varied skills in vocabulary, grammar, reading, and writing often lead to unequal participation and achievement. This study investigated the impact of cooperative learning (CL) on managing proficiency differences in a secondary classroom and explored students’ perceptions of the approach. A pre-experimental one-group pretest–posttest design was employed with 20 tenth-grade students at a public secondary school in Indonesia. The intervention spanned four sessions incorporating Think-Pair-Share, Jigsaw information sharing, and guided peer feedback. Data were collected through a composite proficiency test and a 10-item Likert-scale perception questionnaire. Results showed a substantial improvement in proficiency, with mean scores rising from 56.40 (SD = 11.84) to 82.95 (SD = 6.53), t(19) = 11.56, p < .001, Cohen’s d = 2.58. Classifications shifted from heterogeneous (“Poor,” “Fair,” “Good”) to uniformly higher levels (“Good,” “Very Good”). Student perceptions were predominantly positive, with highest agreement for increased motivation (75%), responsibility (70%), and confidence (65%). These findings demonstrate that short, structured CL interventions can significantly enhance proficiency and foster inclusivity, supporting both sociocultural and cognitive load theoretical perspectives. The study contributes to international debates on equity in language education and offers practical guidance for teachers and policymakers seeking scalable, student-centered strategies for heterogeneous classrooms.